The Effect of Reproductive Health Education on Adolescent’ Attitudes Toward Premarital Sexual Behavior at SMK Ma’arif NU 1 Cilongok - Kesya Nurul Aulia; Mariah Ulfah; Wasis Eko Kurniawan (International Journal Of Health Science, 2026)
Premarital sexual behavior among adolescents remains a reproductive health concern that requires attention. Reproductive health education is expected to influence adolescents’ attitudes toward risky sexual behavior. This study aimed to determine the effect of reproductive health education on adolescents’ attitudes toward premarital sexual behavior at SMK Ma’arif NU 1 Cilongok. This research used a quantitative analytic method with a pre-experimental one group pre-test and post-test design. The sample consisted of 209 respondents selected using a total sampling technique. The instrument used was an attitude questionnaire, and data analysis was performed using the Wilcoxon Signed Rank Test. The results showed that prior to receiving education, most respondents were in the moderate attitude category (92.8%). After the intervention, most respondents shifted into the high attitude category (99.5%). Statistical analysis showed a p-value of 0.000, indicating a significant effect of reproductive health education on adolescents’ attitudes regarding premarital sexual behavior. It is recommended that schools conduct reproductive health education regularly to improve attitudes and awareness among adolescents in preventing risky sexual behavior.